Potencial produtivo de sistemas silvipastoris Na Zona da Mata de Pernambuco - LIMA, Hugo Neves de Barros (2019)
The potential of silvopastoral systems in northeast Brazil needs to be better assessed in order to exploit their full capacity. In this research, we evaluated morphometric measures, the production of firewood and timber and the physical characteristics of wood of the legume species Gliricidia sepium (Jacq.) Steud and Mimosa caesalpiniifolia Benth. in consortium with Brachiaria decumbens Stapf. Nitrogen, C, isotopic composition (δ15N and δ13C), and digestibility of tree leaves after seven years of planting were also analyzed. After adult trees were cut, the morphometric growth of the tree species was evaluated. Additional response variables included N, C, isotopic composition (δ15N and δ13C) and digestibility of tree leaves at 120-day intervals. The effect of shading on biomass production of Brachiaria decumbens Stapf was also evaluated every 56 days, as well as their N, C, isotopic composition (δ15N and δ13C) and digestibility. No statistical effect was found for the timber and firewood production among the studied species (p=0.1190, p=0.1299, p=0.2579, respectively). However, the sabia had the greatest value of wood density for branches with a diameter > 2.55 cm and < 4.13 cm (0.94 g cm-3) and 0.99 g cm-3 in the stems with diameter ≥ 4.14 cm (p<0.0001). The calorific value for sabia was 4.19 kcal g-1 in the branches with diameter > 2.55 cm and < 4.13 cm and 4.31 kcal g-1 in the stems with diameter ≥ 4.14 cm. Gliricidia presented values of 4.08 kcal g-1 in the branches with diameter > 2.55 cm and < 4.13 cm and 4.15 kcal g-1 in the stems with diameter ≥ 4.14 cm (p<0.0001). Leaves of gliricidia (430 g kg-1) were more digestible than leaves of sabia (213 g kg-1) (p=0.0076). The results obtained at the time of the clear cutting of the trees confirmed the contribution of 53 kg N ha-1 fixed by gliricidia and 98 kg N ha-1 by the sabia. The values of δ15N and N were greater in the leaves of the gliricidia (2.9 ‰ and 37 g kg-1) than in the leaves of sabia (1.2 ‰ and 32 g kg-1) (p=0.0253 and p=0.0074), respectively. It was observed greater forage production under full sun (3,193 kg ha-1) compared with the one that underwent excessive shade exposure (1,502 kg ha-1) (p=0.0006). Leaf digestibility of Brachiaria differed only in cycle 6 (503 g kg-1 in the sun and 355 g kg-1 in the shade) (p=0.0027). The morphometric measurements of the regrowth of the legumes showed no difference for the total weight of the leaves (p=0.8603) and weight of the thick stalks (p=0.6157). For the other measurements, gliricidia presented stagnation in the development at the end of the evaluation period, while the sabia had a tendency to maintain development. The “in vitro” digestibility of the young leaves of the gliricidia presented greater digestibility (504 g kg-1) than the sabia (315 g kg-1) (p<0.0001). The N concentration was greater in the leaves (p=0.0007), thin stems (p=0.0050), and thick stems (p=0.0333) of the gliricidia throughout the evaluated period when compared to the same fractions of the sabia. The introduction of the silvopastoral system provided N to the soil through natural fixation. Sabia provided greater biological nitrogen fixation and presented better physical qualities in the wood, however, the gliricidia showed greater nutritive value and better forage digestibility. The adoption of the system also allowed an increase of income through the sale of timber and firewood. The spacing adopted in this experiment for the tree species interfered negatively in the forage production of the brachiaria and this behavior was similar between the two tree species.